Regional versus general anesthesia in patients underwent hip fracture surgery over 80 years old: A retrospective cohort study (Annals of Medical Research, 2021)
None
Keywords: General Anesthesia; Regional Anesthesia; Elderly Patients; Hip Fracture Surgery; Length Of Hospital Stay; Mortality.